On the Amazonian cricket Phalangopsis Serville, 1831 (Orthoptera: Grylloidea: Phalangopsidae): biology, morphology, and a new species - Souza-Dias, Pedro G. B.; Valente, Roberta M.; Bolfarini, Márcio P.; Ruiz, Gustavo R. S. (Zootaxa, 2022)
Phalangopsis mimbypysara n. sp. is described from specimens collected in natural cavities in the region of Altamira and Vitória do Xingu, state of Pará, Brazil. Phalangopsis gaudichaudi Saussure, 1874 is considered nomen dubium. We provide new data about biology, distribution, habitat selection, morphology, and natural history of the genus Phalangopsis.